From grey literature to peer-reviewed evidence: bridging the monitoring gap of nature-based solutions for Kenya’s water resources - Okello, Cornelius; Sithole, Simangele; Owuor, Margaret Awuor (Frontiers in Environmental Science, 2025)
Nature-based solutions (NbS) are increasingly adopted across Africa to address water security challenges and biodiversity conservation and offer sustainable alternatives to traditional grey infrastructure. Government and non-governmental bodies have implemented interventions such as wetland restoration, afforestation, and rainwater harvesting in Kenya. However, published research outputs in peer-reviewed literature and academic documentation of long-term monitoring remain limited despite widespread field activity. Most data are confined to grey literature such as consultancy reports, donor dashboards, and internal evaluations, hindering comparative analysis, policy integration, and evidence-based scaling. This paper highlights Kenya as a case study to explore the disconnect between NbS implementation and scholarly dissemination. It identifies key challenges: lack of standardised monitoring protocols, fragmented institutional responsibilities, limited technical capacity, insecure data systems, and inadequate policy frameworks. Land tenure complexities and the underutilisation of community knowledge further constrain monitoring efforts. Additionally, the publication gap driven by structural barriers to academic writing and dissemination limits the visibility of local insights. To bridge these gaps, the paper proposes a strategic framework centred on three pillars: (1) institutionalising adaptive monitoring through living labs, (2) developing a national open-access NbS data repository, and (3) embedding standardised NbS indicators into policy, planning, and financing instruments. The paper calls for policy reforms, capacity building, and sustainable (long-term) financing to enable integration of grey literature into academic channels. Strengthening monitoring, evaluation, and learning (MEL) systems is essential to mainstreaming NbS into Kenya’s water governance and achieving resilient, inclusive development outcomes.